Grandmother's Diet Matters: Early Life Programming with Sucrose Influences Metabolic and Lipid Parameters in Second Generation of Rats - Školníková, Elena; Šedová, Lucie; Šeda, Ondřej (Nutrients, 2020)
Early life exposure to certain environmental stimuli is related to the development of alternative phenotypes in mammals. A number of these phenotypes are related to an increased risk of disease later in life, creating a massive healthcare burden. With recent focus on the determination of underlying causes of common metabolic disorders, parental nutrition is of great interest, mainly due to a global shift towards a Western-type diet. Recent studies focusing on the increase of food or macronutrient intake don't always consider the source of these nutrients as an important factor. In our study, we concentrate on the effects of high-sucrose diet, which provides carbohydrates in form of sucrose as opposed to starch in standard diet, fed in pregnancy and lactation in two subsequent generations of spontaneously hypertensive rats (SHR) and congenic SHR-Zbtb16 rats. Maternal sucrose intake increased fasting glycaemia in SHR female offspring in adulthood and increased their chow consumption in gravidity. High-sucrose diet fed to the maternal grandmother increased brown fat weight and HDL cholesterol levels in adult male offspring of both strains, i.e., the grandsons. Fasting glycaemia was however decreased only in SHR offspring. In conclusion, we show the second-generation effects of maternal exposition to a high-sucrose diet, some modulated to a certain extent by variation in the Zbtb16 gene.
Keywords: Rats; Maternal Nutritional Physiological Phenomena; dieta; lipidy; glukózový toleranční test; krevní glukóza; Male; těhotenství; náchylnost k nemoci; Dietary Sucrose; mužské pohlaví; Energy Metabolism; tělesné váhy a míry; rat model; konzumní sacharóza; krysa rodu Rattus; Lipids; DOHAD; energetický metabolismus; Blood Glucose; Lipid Metabolism; ženské pohlaví; zvířata; Humans; brown fat; Pregnancy; high sucrose diet; zpožděný efekt prenatální expozice; metabolismus lipidů; Disease Susceptibility; metabolické nemoci; HDL cholesterol; Metabolic Diseases; Diet; Female; Glucose Tolerance Test; fyziologie výživy v mateřství; Prenatal Exposure Delayed Effects; lidé; Body Weights and Measures; Animals